Analisis Kepatuhan Syari’ah Pada Mekanisme Transaksi E-Commerce Halal Di Indonesia : Studi Literatur Dan Fatwa DSN-MUI - Anggriyani, Dewi; Muhajir, Ali Achmad (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2026)
The rapid growth of the digital economy ecosystem in Indonesia, with a projected Gross Merchandise Value (GMV) reaching 90 billion by 2024, has created a fundamental transformation in people's transaction patterns from conventional to digital. This phenomenon brings new urgency to Islamic law discussions, especially regarding the uncertainty (gharar) that arises due to the loss of physical interaction and the potential for usury in digital payment instruments. This study aims to critically analyze the transaction mechanisms on marketplace platforms in Indonesia to ensure their compliance with the principles of fiqh muamalah and the normative standards of the DSN-MUI Fatwa, specifically Fatwa No. 110/DSN-MUI/IX/2017 concerning Buying and Selling and Fatwa No. 116/DSN-MUI/IX/2017 concerning Electronic Money (National Sharia Council Fatwa No: 20/DSN-MUI/IV/2001 Concerning Guidelines for Implementing Investments for Sharia Mutual Funds, 2001). Using qualitative methods and a library research approach, this study analyzes Terms and Conditions documents and contemporary fiqh literature to test the validity of the contract. Key findings from this study indicate that the architecture of modern e-commerce transactions has inherently adopted the principle of Bai' as-Salam contracts, where the potential for gharar is mitigated through detailed and specific product descriptions . Furthermore, this study confirms that the digital ijab qabul mechanism through a click action ('buy' or 'checkout') is valid according to sharia as a mu'athah contract based on custom ('urf) and willingness . However, research also identified a critical area in e-wallet usage, where promotions in the form of discounts and cashback could potentially fall into usury if the underlying deposit contract is a loan (qardh) that requires additional benefits, unless it is purely a marketing strategy (ju'alah) without binding conditions. Finally, the dispute resolution and return features are identified as modern manifestations of the rights of khiyar 'aib and khiyar ru'yah, which guarantee the protection of Muslim consumers.